Lutzomyia wellcomei Fraiha, Shaw & Lainson (Diptera, Psychodidae, Phlebotominae) em Fragmento de Mata Atlântica do Rio Grande do Norte, Nordeste do Brasil - Marcos Paulo Gomes Pinheiro; José Hilário Tavares da Silva; Vanessa da Escóssia Pegado Silva; Maria Jaqueline de Andrade; Maria de Fátima Freire de Melo Ximenes (EntomoBrasilis, 2013)
Leishmaniasis can affect humans and animals in visceral or cutaneous forms. The cutaneous form has been associated, among other species, with Lutzomyia wellcomei Fraiha, Shaw & Lainson, initially found in the Amazon region. The present study is based on monthly collections from January to December in an Atlantic Forest remnant and a peridomestic environment, using CDC light traps. This is the first systematized study of the specie in Rio Grande do Norte State. The insects were metalized under carbon tape, visualized and photographed with a scanning electron microscope. The most abundant species in the forest area was Lutzomyia walkeri Newstead followed by L. wellcomei. Of the total captured in the forest and the peridomestic environment, around 8% were L. wellcomei, the predominant species in the forest environment in the rainy season. L. wellcomei sandflies were not captured in the peridomestic environment. In the forest this species was found along with Lutzomyia whitmani Antunes & Coutinho and Lutzomyia intermedia Lutz & Neiva. Male and female Lutzomyia longipalpis Lutz & Neiva were predominant in the peridomestic environment. Microscopic analysis of the external morphology of L. wellcomei reveals details of male and female heads. Lutzomyia wellcomei Fraiha, Shaw & Lainson (Diptera, Psychodidae, Phlebotominae) em fragmento de Mata Atlântica do Rio Grande do Norte, Nordeste do Brasil Resumo. As leishmanioses podem afetar seres humanos e animais nas formas visceral e tegumentar. A forma tegumentar tem sido associada, entre outras espécies, a Lutzomyia wellcomei Fraiha, Shaw & Lainson, inicialmente encontrado na região amazônica. O estudo se baseou em coletas mensais de janeiro a dezembro em um fragmento de Mata Atlântica e em um ambiente peridomiciliar, com armadilhas luminosas CDC. Esse é o primeiro estudo sistematizado sobre essa espécie no Rio Grande do Norte. Os insetos foram identificados e analisados em relação às chuvas no local. Alguns espécimes de L. wellcomei foram metalizados sob fita de carbono, visualizados e fotografados em microscópio eletrônico de varredura. A espécie mais abundante na área de mata foi Lutzomyia walkeri Newstead seguida por L. wellcomei. Do total capturado no ambiente de mata e no peridomicílio, cerca de 8% corresponde a L. wellcomei, sendo esta a espécie predominante no ambiente de mata no período chuvoso. Flebotomíneos L. wellcomei não foram capturados em ambiente peridomiciliar. Na mata essa espécie foi encontrada juntamente às espécies Lutzomyia whitmani Antunes & Coutinho e Lutzomyia intermedia Lutz & Neiva. Machos e fêmeas Lutzomyia longipalpis Lutz & Neiva foram predominantes no ambiente peridomiciliar. A análise microscópica da morfologia externa de L. wellcomei revela detalhes da cabeça de machos e fêmeas.